Gender differences in the physiological responses and kinematic behaviour of elite sprint cross-country skiers - Sandbakk, O.; Ettema, G.; Leirdal, S.; Holmberg, H. C. (European Journal of Applied Physiology, 2012)
Gender differences in performance by elite endurance athletes, including runners, track cyclists and speed skaters, have been shown to be approximately 12%. The present study was designed to examine gender differences in physiological responses and kinematics associated with sprint cross-country skiing. Eight male and eight female elite sprint cross-country skiers, matched for performance, carried out a submaximal test, a test of maximal aerobic capacity (VO2max) and a shorter test of maximal treadmill speed (V max) during treadmill roller skiing utilizing the G3 skating technique. The men attained 17% higher speeds during both the VO2max and the V max tests (P < 0.05 in both cases), differences that were reduced to 9% upon normalization for fat-free body mass. Furthermore, the men exhibited 14 and 7% higher VO2max relative to total and fat-free body mass, respectively (P < 0.05 in both cases). The gross efficiency was similar for both gender groups. At the same absolute speed, men employed 11% longer cycles at lower rates, and at peak speed, 21% longer cycle lengths (P < 0.05 in all cases). The current study documents approximately 5% larger gender differences in performance and VO2max than those reported for comparable endurance sports. These differences reflect primarily the higher VO2max and lower percentage of body fat in men, since no gender differences in the ability to convert metabolic rate into work rate and speed were observed. With regards to kinematics, the gender difference in performance was explained by cycle length, not by cycle rate.